HUBUNGAN AGAMA DAN NEGARA DALAM PERSPEKTIF PEMIKIRAN SAYYID QUTUB - Sarif Sarif (Sekolah Pasca Sarjana IAIN Bengkulu, 2016)
Abstract: Religion Andstaterelations In The Perspectiveof Sayyid Qutb. This paper discusses the main points of Sayyid Qutb thought of religion as the foundations of the state and his thoughts about the relationship between religion and state. This type of research is library researchby using literature as the primary data in the research, and studies are presented in descriptive analysis. The method used in this study is a qualitative approach to history. From the results of this study found that, according to Sayyid Qutb, religion must be the basis for the formation of a government. For Sayyid Qutb, to obtain the title of an Islamic government, a community or a country should be run in accordance to the rules and the laws of God. Furthermore, Sayyid Qutb mentioned three aspects that can be classified as the principles of the Islamic government, namely justice authorities, the obedience of the people, and deliberations between the authorities and the people. Sayyid Qutb also recommended that a political power in the state must be in accordance with religious teachings, because the religion and state have interlocking relationships.